Quality of life of patients with hip fracture was better during the COVID-19 period than before, an ancillary study from the HiFIT multicenter study - Lasocki, Sigismond; Capdevila, Xavier; Bijok, Benjamin; Lahlou-Casulli, Maria; Collange, Vincent; Grillot, Nicolas; Loupec, Thibault; Rineau, Emmanuel; Léger, Maxime; , the HiFIT Investigators; Angers, CHU; BOUHOURS, Guillaume; et al. (Frontiers in Public Health, 2024)
The COVID-19 pandemic had a global impact on people life, notably because of lockdown periods. This could particularly affected patients suffering from hip fracture, who could have been more isolated during these periods. We aim at evaluating the impact of the COVID-19 period (including lockdown periods) on quality of life (QOL) in elderly patients 90 days after a surgery for a hip fracture.Subject and Methods :Ancillary study of the prospective randomized controlled HiFIT study. We compared the QOL measured at 90 days after a hip fracture surgery using the EuroQOL-5 dimensions 3 levels (EQ-5D), the Perceived Quality of life (PQOL) and the Instrumental Activities of Daily Living (IADL) in patients included in the Hifit study before and during the COVID-19 pandemic.The characteristics of the 161 patients included before and of the 213 included during the COVID period (including 122 (57%) during COVID with containment periods and 91(43%) during COVID without containment periods) were similar (mean age 84±10 years; 282 (75%) women). The majority (81%) of the patients alive at 90 days had returned to their previous place of residence in both periods. During the COVID period, EQ-5D showed better patient pain/discomfort and anxiety/depression levels. The PQOL happiness was not different, with around 81% of the patient being "happy" or "very happy" during the two periods and the IADL was also similar during the two periods. In the multivariate analysis odd ratios of having poorer outcomes were increased before COVID for pain/discomfort (OR 2.38,, p=0.001), anxiety ], p=0.017) and mobility (1.69 [1.02 -2.86], p = 0.044).Patient's quality of life measured using different scales was not altered during the COVID period compared to before COVID, 90 days after a hip fracture. Surprisingly, the Pain/Discomfort and Anxiety dimensions of the EQ-5D questionnaires were even better during the COVID period.